Community learning centre in improving disasters awareness through environmental education. Issue 1 (March 2021) - Akbar, Z
Abstract: The Community Learning Center is a non-formal education program that aims to expand the reach of education in the community by involving community participation. Environmental education is one of the materials given to students in this centre. This can be an opportunity to increase community disaster awareness especially in relation to floods disaster that often occur in the area. The purpose of this paper is to find out: (1) Strategies to increase the role of community learning centre in improving disaster awareness through environmental education, (2) Environmental education that can be utilized in increasing disaster awareness in community learning centre in East Jakarta, (3) Factors supporting and inhibiting strategies for improving disaster awareness through environmental education at community learning centre.